Financial Performance On Banking Share Price - Handayani, Asih; Winingrum W.A, Sri Putri (Universitas Ibn Khladun Bogor, 2023)
This study aims to identify the impact of financial performance on stock prices, especially in banking companies listed on the Indonesia Stock Exchange. Financial performance proxied by TATO, ROA and DER is tested using the classic assumption test to determine the effect on stock prices either partially or simultaneously. The research method used was descriptive quantitative and data testing was carried out using panel data regression with the equation Y = -12709.89X3 – 2100.702X3 – 4.710816X3. The test results have proven that both partially and simultaneously the independent variables have an influence but are very weak on the dependent variable.